2018
DOI: 10.1002/2017jc013396
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale and Submesoscale Processes in the Southeast Atlantic and Their Impact on the Regional Thermohaline Structure

Abstract: The turbulent processes in the Cape Basin, the southeasternmost gate of the Atlantic Ocean, play a key role in the transport and mixing of upper to intermediate water masses entering the area from the Indian Ocean, making them especially relevant for the Indo‐Atlantic transfer of heat and salt. In this paper, two numerical simulations at different horizontal resolutions are used to study mesoscale and submesoscale dynamics, their phenomenology, their evolution, and their impact on the local water masses. Subme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 96 publications
(180 reference statements)
2
27
0
Order By: Relevance
“…The signal of present-day satellite altimetry exceeds the associated noise at scales larger than about 50 km in the greater Agulhas region (Dufau et al, 2016). Dufau et al (2016) further point out that in winter time, when the submesoscale dynamics are most active (Callies et al, 2015), the rough sea state shifts this signal-equals-noise scale to even larger scales. Present-day altimetry is thus not able to resolve submesoscale dynamics.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The signal of present-day satellite altimetry exceeds the associated noise at scales larger than about 50 km in the greater Agulhas region (Dufau et al, 2016). Dufau et al (2016) further point out that in winter time, when the submesoscale dynamics are most active (Callies et al, 2015), the rough sea state shifts this signal-equals-noise scale to even larger scales. Present-day altimetry is thus not able to resolve submesoscale dynamics.…”
Section: Introductionmentioning
confidence: 90%
“…Ro > 1 are found to occur only barely in INALT20r.L46.HighDiff (Figure 2a); on average in only 0.17% of the domain area ( Figure 2b). A snapshot of the surface Rossby number on the model day 4 September 2012 shows that even in the Southern Hemisphere winter, when the submesoscales should be most active (Callies et al, 2015), the surface flow is mainly associated with low Rossby numbers and small-scale features are almost absent from the simulation (Figure 3a). There are no submesoscale flows simulated in the Agulhas…”
Section: The Nonsubmesoscale-resolving (1/20) • Experiments (Inalt20rmentioning
confidence: 99%
See 1 more Smart Citation
“…This 1 mm threshold step is a bit smaller than the typical value used in the literature; however, recent work has shown that it leads to more accurate eddy sizes and amplitudes (Faghmous et al, 2015). This criterion prevents the misidentification of large eddies as two smaller ones (Chaigneau et al, 2008(Chaigneau et al, , 2009. The spatially largest closed ADT contour line encompassing one extremum corresponds to the eddy edge.…”
Section: Mooring 1 -M1mentioning
confidence: 98%
“…The sea surface height (SSH) and geostrophic velocity fields are derived from the Delayed Time Maps of Absolute Dynamic Topography (MADT) mapped daily on a 1/4 • Mercator grid (Pujol et al, 2016). An eddy detection method based on the algorithm developed by Chaigneau et al (2008Chaigneau et al ( , 2009 was applied to these absolute dynamic topography (ADT) fields. This new method detects local ADT extrema to identify potential eddy centers.…”
Section: Mooring 1 -M1mentioning
confidence: 99%